Panorama of risky sexual behaviors in the Brazilian adult population - PNS 2019 - Nayara Lopes Gomes; Claudia de Souza Lopes (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To describe the risky sexual behaviors of Brazilian adults according to socioeconomic, demographic, and regional characteristics. METHODS Data from the 2019 National Health Survey, referring to the population aged 18 years or older, were analyzed. Risky sexual behaviors were considered: early sexual initiation, before the age of 15 years, and nonuse of condoms in the last sexual intercourse. Prevalence and respective confidence intervals were calculated for the subgroups of interest. RESULTS Early sexual initiation among adult individuals was 24% among men and 11% among women, being higher among young people with lower levels of education and household income. The nonuse of condoms was higher among married/cohabiting partners, no schooling or with some elementary school, and among older people. The prevalence of nonuse of condoms among married/cohabiting partners was the same in both sexes (75%). However, among non-cohabiting partners, gender disparity was relevant, as 39.1% of women did not use condoms in the last sexual intercourse, while among men this result was 26.9%. CONCLUSIONS Higher prevalence of early sexual initiation for younger generations is noteworthy, especially among women. Concerning the nonuse of condoms, there are important gender disparities in the group of non-cohabiting partners, in addition to the high prevalence among older people, which should be considered in the formulation of public policies. The results of the present study are extremely relevant for understanding the adult population currently more vulnerable to sexually transmitted infections, after over five years without official statistics on this matter at the national level.